Representation of Motivation through Natural Imagery in the Lyrics of the Song "Tasna'o Almustaheel" by Hamza Namira and Humood Alkhudher - Affurqand, Muhammad Daffa; Shofiyuddin, Haris (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to analyze natural imagery as a medium for conveying motivational messages in the Arabic song lyrics Tasna’o Almustaheel by Hamza Namira and Humood AlKhuder. The study employs a qualitative descriptive method with a stylistic approach through textual analysis of the song lyrics. The data consist of lyric excerpts containing natural imagery such as rivers, water, the Thurayya star, rain, the sky, and moonlight, collected using the observation and note-taking technique. The results show that natural imagery in the lyrics is dominated by visual and symbolic imagery. The imagery of rivers and water represents flowing and strengthening hope, while the imagery of the sky and stars symbolizes lofty aspirations. Rain imagery depicts social benefit for others, whereas moon imagery signifies the role of individuals as sources of inspiration. These findings indicate that the use of natural imagery functions effectively as an aesthetic strategy to reinforce motivational messages in Arabic song texts.